Criteria used by venture capitalists to evaluate new venture proposals - Macmillan, Ian C.; Siegel, Robin; Narasimha, P.N.Subba (Journal of Business Venturing, 1985)
A questionnaire was administered to one hundred venture capitalists to determine the most important criteria that they use to decide on funding new ventures. Perhaps the most important finding from the study is direct confirmation of the frequently iterated position taken by the venture capital community that above all it is the quality of the entrepreneur that ultimately determines the funding decision. Five of the top ten most important criteria had to do with the entrepreneur's experience or personality. There is no question that irrespective of the horse (product), horse race (market), or odds (financial criteria), it is the jockey (entrepreneur) who fundamentally determines whether the venture capitalist will place a bet at all. The question is if this is the case, then why is so much emphasis placed on the business plan? In a business plan there is generally little to indicate the characteristics of the entrepreneur—it is generally devoted to a detailed discussion of the product/service, the market, and the competition. To us, the implications are obvious—such content is necessary, but not sufficient. The business plan should also show as clearly as possible that the “jockey is fit to ride” —namely, indicate by whatever feasible and credible means possible that the entrepreneur has staying power, has a track record, can react to risk well, and has familiarity with the target market. Failing this, he or she needs to be able to pull together a team that has such characteristics and show that he or she is capable of leading that team. Factor analysis of the results indicate that venture capitalists appear to assess ventures systematically in terms of six categories of risk to be managed. These are: risk of losing the entire investment: risk of being unable to bail out if necessary; risk of failure to implement the venture idea; competitive risk; risk of management failure; and risk of leadership failure. Finally, three clusters of venture capitalists were identified: those who carefully assess the competitive and implementation risks: those who seek easy bail out; and those who deliberately keep as many options open as possible.